Analysis of two case studies of sexual abuse committed by mothers - Nicoletti, Marcela (2017)
This article aimed to analyze two cases of sexual abuse against girls, one with three years old and another with six years old, which was perpetrated by their progenitors, and examined by a psychosocial team of a South Brazilian Forum. In both cases the mothers had a family history of incestuous sexual abuse, were living alone with their daughters and the proper disclosure of the abuse committed against the girls only happened after the guard reversal. The fathers showed a passive behavior against the ex-wives and they were still sexually attached to them. With regard to the sexual violence, they had trouble believing it had been perpetrated by the mothers. It was also observed the difficulty of specialized services (police stations) to receive and register the complaint